If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 9 = 6x + 25 Reorder the terms: 9 + 10x = 6x + 25 Reorder the terms: 9 + 10x = 25 + 6x Solving 9 + 10x = 25 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 9 + 10x + -6x = 25 + 6x + -6x Combine like terms: 10x + -6x = 4x 9 + 4x = 25 + 6x + -6x Combine like terms: 6x + -6x = 0 9 + 4x = 25 + 0 9 + 4x = 25 Add '-9' to each side of the equation. 9 + -9 + 4x = 25 + -9 Combine like terms: 9 + -9 = 0 0 + 4x = 25 + -9 4x = 25 + -9 Combine like terms: 25 + -9 = 16 4x = 16 Divide each side by '4'. x = 4 Simplifying x = 4
| 10x-22=68 | | x^2+x+2+x+2=100 | | x(x-5)=36 | | 4x^2-6x+2=0 | | 3(n+2)+4n=4(n+2)+4 | | 41+2(3x+6)=95 | | 2(3)-2(4x)+7=0 | | (2*a)+17= | | 3(n+2)-2=4(n-4)-4(n-11) | | 118-(3*b)= | | x(x-8)=-15 | | -3x^2+36x-72=0 | | 25x^2=100 | | 8(2x-1)=72 | | X+46=72 | | 5d-3.3=7.5 | | 17x-8x-9=76-40 | | n=15+2m-4 | | 5(3c-c)+3=43 | | (3x+2)(x+1)=4 | | 2w+9w+2w+8w+7w+w= | | 4a-2=7a-6 | | 6f+30=2f-8 | | 4(x+7.50)=40 | | 118-(3xb)= | | 4x-8=x+25 | | 49-2x=7x+16 | | 11-10x=103-38x | | 139-3x=6x+22 | | 2x+3(x-1)=27 | | 3(1+Y)=3-(5y+2) | | -17=-5+4u |